VUV 157 nm laser ablation of composite structures - Cockcroft, S.; Walton, C.D.; Zakaria, R. (Springer, 2010)
We report on the laser ablation of composite prismatic structures using a vacuum ultraviolet (VUV) 157 nm F(2) laser. Polycarbonate and CR-39 substrates have been intentionally seeded with silver wires and silicon carbide whiskers respectively. The seed particles remain attached to the underlying substrate after laser ablation, forming composite silver-polycarbonate and silicon carbide-CR-39 interfaces. Strong optical absorption at 157 nm in the polymeric substrates allows precise control over the depth between the base of the substrate and composite interface. The surface roughness of the as-received seed particles has a significant effect on the final surface quality of the ablated structures. The textured surface on the silicon carbide whiskers is resolved on the walls of the ablated structures. This is in contrast to the composite structures formed using silver wires, which have a comparatively smoother surface.